Scaling up HIV viral load – lessons from the large‐scale implementation of HIV early infant diagnosis and CD4 testing. (12th November 2017) - Peter, Trevor; Zeh, Clement; Katz, Zachary; Elbireer, Ali; Alemayehu, Bereket; Vojnov, Lara; Costa, Alex; Doi, Naoko; Jani, Ilesh
Abstract: Introduction: The scale‐up of effective HIV viral load (VL) testing is an urgent public health priority. Implementation of testing is supported by the availability of accurate, nucleic acid based laboratory and point‐of‐care (POC) VL technologies and strong WHO guidance recommending routine testing to identify treatment failure. However, test implementation faces challenges related to the developing health systems in many low‐resource countries. The purpose of this commentary is to review the challenges and solutions from the large‐scale implementation of other diagnostic tests, namely nucleic‐acid based early infant HIV diagnosis (EID) and CD4 testing, and identify key lessons to inform the scale‐up of VL. Discussion: Experience with EID and CD4 testing provides many key lessons to inform VL implementation and may enable more effective and rapid scale‐up. The primary lessons from earlier implementation efforts are to strengthen linkage to clinical care after testing, and to improve the efficiency of testing. Opportunities to improve linkage include data systems to support the follow‐up of patients through the cascade of care and test delivery, rapid sample referral networks, and POC tests. Opportunities to increase testing efficiency include improvements to procurement and supply chain practices, well connected tiered laboratory networks with rational deployment of test capacity across different levels of health services, routine resource mapping and mobilization to ensure adequate resources for testing programs, and improved operational and quality management of testing services. If applied to VL testing programs, these approaches could help improve the impact of VL on ART failure management and patient outcomes, reduce overall costs and help ensure the sustainable access to reduced pricing for test commodities, as well as improve supportive health systems such as efficient, and more rigorous quality assurance. These lessons draw from traditional laboratory practices as well as fields such as logistics, operations management and business. Conclusions: The lessons and innovations from large‐scale EID and CD4 programs described here can be adapted to inform more effective scale‐up approaches for VL. They demonstrate that an integrated approach to health system strengthening focusing on key levers for test access such as data systems, supply efficiencies and network management. They also highlight the challenges with implementation and the need for more innovative approaches and effective partnerships to achieve equitable and cost‐effective test access.